Uma análise sobre utilização de veículo híbrido na matriz de transportes da UFG Campus Samambaia: economicidade aliada à sustentabilidade - (:unkn) unknown (Universidade Federal de Goiás, 2016)
The current world situation distinguishes itself through measures that preserve natural resources and they can be less harmful to the environment. This view could not be different for the auto industry, which in turn accounts for 5% of the brazilian GDP, employs over 1.5 million people and receives prominent position worldwide. Now exist a greater concern to produce more energy efficient vehicles and less polluting. Emerge hybrid vehicles as a possible solution to the chaos seen in large cities, appearing the car as the biggest polluter. However, some drawbacks, mainly linked to car price formation, still hinder the access of a majority of the population to the type of hybrid powertrain. In this sense this research analyzes to verify how behave a possible gradual replacement of vehicles for a vehicle fleet composed entirely by internal combustion vehicles for other hybrids. And then proposes such action in a higher education institution (IFES), the Federal University of Goiás (UFG), which was observed the main variables for six possible scenarios, where 20% of the existing fleet would be gradually replaced, for a sample that is 20.48%of the total to reach the completeness with hybrid vehicles. This proved that the hybrids are more efficient in all the proposals made, but that the high cost of purchasing replacement make it impossible for a short term, requiring more than six years of use.
An analysis about use of hybrid vehicle in matrix transports in UFG Campus Samambaia: economic viability allied to sustainability
Keywords: Veículos híbridosT; Transporte; Economia; Sustentabilidade; Hybrid Vehicle; Transport; Economy; Sustainability; ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS